Dietary Antioxidants and Nrf2-Related Redox Responses in Sheep: Evidence, Limitations, and Implications for Health and Productivity - Shahab Ur Rehman; Aftab Shaukat; Mohamed Tharwat; Asfand Yar Khan; Abdulrahman A. Alkheraif; Rahmat Ali (Veterinary Sciences, 2026)
Oxidative imbalance can accompany physiologically demanding and environmental transitions in sheep, but its magnitude varies with tissue, production stage, diet, health status, and the biomarkers used. Nuclear factor erythroid 2-related factor 2 (Nrf2; encoded by NFE2L2) coordinates inducible cytoprotective responses through Kelch-like ECH-associated protein 1 (Keap1), antioxidant response elements (AREs), and Keap1-independent regulatory routes. This structured narrative review evaluates whether dietary antioxidants engage Nrf2-related responses in sheep and whether such responses translate into health, productivity, or product-quality benefits. Evidence was classified by model and endpoint. Tier 1 comprised ovine dietary interventions with tissue-level Nrf2-pathway measurements; Tier 2 comprised ovine dietary studies with redox or phenotypic outcomes but no pathway assay; Tiers 3 and 4 comprised other-ruminant and non-ruminant or in vitro mechanistic evidence, respectively. Only rutin in transition-period ewes and a water extract of Artemisia annua in lambs met Tier 1 criteria. Both altered Nrf2-related gene expression, but neither used pathway perturbation, DNA-binding assays, or definitive target-engagement methods; the results therefore indicate association rather than causality. Evidence for tannins, essential oils, vitamins, selenium, carotenoid-rich feeds, and other phytochemicals in sheep is broader for oxidative status and product stability than for Nrf2 activation. Growth, fertility, milk yield, and survival outcomes are heterogeneous and strongly context-dependent. Dietary antioxidants may act through direct radical interception, microbial metabolites, metal chelation, membrane protection, mitochondrial effects, receptor signaling, inflammation control, and, in some settings, Nrf2-related adaptation. Future studies should combine dose–response designs, exposure measurements, multiple redox markers, tissue-specific pathway assays, and causal validation. Accordingly, Nrf2 is a plausible mechanistic framework for sheep nutrition, but current evidence does not support broad causal or productivity claims.